Lateral septum microglial changes and behavioral abnormalities of mice exposed to valproic acid during the prenatal period - Le?o, Ellen Rose Leandro Ponce de (Elsevier, 2021)
Most animal model studies of autism spectrum disorder (ASD) have been performed in males, which may be a reflex of the 3-times higher prevalence in boys than in girls. For this reason, little is known about the mechanisms underlying disease progression in females, and nothing is known about potential associations between microglial changes in the lateral septum (LS) and adult female cognition. Prenatal exposure to valproic acid (VPA) in mice has been widely used as an experimental model of autism-like behaviors associated with cellular changes. However, no study has reported the influence of VPA exposure in utero and its consequences on limbic system-dependent tasks or the microglial response in the LS in adult female mice. We compared the exploratory activity and risk assessment in novel environments of BALB/c control mice to mice exposed in utero to VPA and estimated the total number of microglia in the LS using an optical fractionator. On day 12.5 of pregnancy, females received diluted VPA or saline by gavage. After weaning, VPA exposed or control pups were separately housed in standard laboratory cages. At 5 months of age, all mice underwent behavioral testing and their brain sections were immunolabelled using IBA-1 antibody. In the open field test, VPA group showed a greater distance traveled, which was accompanied by less immobility, less time spent on the periphery and a greater number, crossed lines. Similar findings were found in the elevated plus maze test, where VPA mice traveled greater distances, immobility was significantly higher than that of control and VPA group spent less time on the closed arms of apparatus. Stereological analysis demonstrated higher microglial total number and density in the LS of VPA mice, as the cell count was greater, but the volume was similar. Therefore, we suggest that an increase in microglia in the LS may be part of the cellular changes associated with behavioral dysfunction in the VPA model of ASD.